2014
DOI: 10.1007/s11661-014-2407-x
|View full text |Cite
|
Sign up to set email alerts
|

On the Modeling of the Diffraction Pattern from Metal Nanocrystals

Abstract: The powder diffraction patterns of spherical nanocrystals made of five different fcc metals were generated using atomistic models within a Molecular Dynamics simulation. Static and dynamic effects are interpreted and discussed within the framework of two different approaches, respectively, based on (1) a Reciprocal Space and (2) a Direct Space representation of diffraction. Chosen elements display a wide range of properties, especially related to material stiffness and elastic anisotropy, so to deeply challeng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 40 publications
2
7
0
1
Order By: Relevance
“…For comparison, the values for the unfaulted model are provided: 3.41 (423 K), 3.05 (473 K), 3.06 (523 K). agreement with the values found in our samples and in other recent reports (Gelisio & Scardi, 2014). In our study, the size dependence of the lattice parameters is mostly due to the large number of Pt atoms lying on the surface of the smallest SPH NCs, and was determined through the strain model implemented in DEBUSSY (Cervellino et al, 2015) and reported in equation (7):…”
Section: Figuresupporting
confidence: 92%
See 2 more Smart Citations
“…For comparison, the values for the unfaulted model are provided: 3.41 (423 K), 3.05 (473 K), 3.06 (523 K). agreement with the values found in our samples and in other recent reports (Gelisio & Scardi, 2014). In our study, the size dependence of the lattice parameters is mostly due to the large number of Pt atoms lying on the surface of the smallest SPH NCs, and was determined through the strain model implemented in DEBUSSY (Cervellino et al, 2015) and reported in equation (7):…”
Section: Figuresupporting
confidence: 92%
“…(iii) Surface relaxation effects are reported in very small nanoparticles that, in metals, typically (but not uniquely) lead to average lattice parameters shorter than in the bulk material, giving rise to a (material-dependent) contraction of the metalmetal distances at the surface (Solliard & Flueli, 1985;Qi & Wang, 2005;Qi et al, 2002;Gelisio & Scardi, 2014). A sizedependent effect was modelled for the SPH population by optimizing the two parameters of equation (7) (see below), with a homogeneous shrinkage within each cluster of a defined size.…”
Section: A Multicomponent Model For the Dfa Of Pt@sio 2 Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] As already pointed out, the powder pattern of G35 after energy minimization ( Figure 5) includes effects of an inhomogeneous strain due to grain boundaries and grain-to-grain interactions. [20] Similar effects are also present in the case of an isolated G35 grain, where surface atomic positions are modified by surface tension forces (lower coordination number of surface atoms, causing the so-called surface relaxation effect [39,40] ). We can account for these complex effects, causing a relatively small but measurable strain broadening (or microstrain) component, in a simplified but sufficiently flexible way.…”
Section: Powder Pattern Modelingmentioning
confidence: 80%
“…[20] Modeling results are equally good for the isolated G35 (not shown here for briefness), where the microstrain is caused by the free surface. [40,43] Corresponding rms displacement trends are shown in Figure 8…”
Section: Powder Pattern Modelingmentioning
confidence: 99%